MENELISIK FENOMENA PERCERAIAN PADA AKTOR PERNIKAHAN DINI DALAM PERSPEKTIF STRUKTURAL FUNGSIONAL - Abdullah, Mirna Nur Alia (Universitas Hamzanwadi, 2022)
Early marriage is generally carried out by young couples who are not mentally and physically ready to build a quality household. The purpose of this study is to examine and explain the phenomenon of divorce in early marriage cases based on functional structural theory. The method used in this research is a literature study, which is the process of selecting, reading, recording and collecting references that are relevant to the topic of study as a data source. The results of the study state that until now, divorce has become one of the crucial problems considering the negative impact caused after divorce is very complex, especially in cases of divorce that occur in actors who previously underwent young marriages. Functional structural theory views that divorce occurs because of an imbalance in the family. In addition, early marriage has a higher potential for divorce due to the lack of individual readiness, so that instability in the family occurs more often, in this case early marriage is prone to divorce. Therefore, to realize a harmonious marriage based on a functional structural perspective, it is necessary to balance the system to achieve this goal.